PENGGUNAAN LIMBAH IKAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI PUTIH (Brassica chinensis L.) - Silvanus Titus Ora Pae; Agustinus J.P Ana Saga (AGRICA, 2017)
The basic problem of farmers in Ende Regency is the availability of fertilizer. Difficult to get fertilizer affects the production of white mustard declines. This study aims to determine the effect of fish waste fertilizer doses on the growth and production of chicory plants and find out the optimum dose of fish waste fertilizer in increasing the growth and yield of chicory plants. The treatment used is K0 = 0 liters / plot (control), K1 = 5000 liters / ha or equivalent to 2.5 liters / plot. K2 = 10,000 liters / ha or equivalent to 5.0 liters / plot. K3 = 15,000 liters / ha or equivalent to 7.5 liters / plot. K4 = 20,000 liters / ha or equivalent to 10.0 liters / plot. The results showed that the provision of fish waste had an effect on the percentage increase in plant growth by 1.38%, the average number of leaves was 0.72%, the average leaf area was 1.42%, average crop diameter was 10, 00%, the average percentage of fresh stover tonnes 1 ton is 3.23%, the average percentage of fresh stover weight of ha-1 is 2.04%. While the administration of fish waste doses of 10,000 ltr ha-1 has not shown growth and optimal results and doses of 20,000 ltr / hr give growth of plant height of 24.64 cm, the number of leaves is 16.02 strands, leaf area is 118.70 cm , crop diameter is 18.00 cm, fresh weight of plant stover is 0.49 kg/plant, fresh weight of plant stover per hectare is 50.06 tons/ha.